Dynamic Interactions Between Financial Development and Current Account Sustainability in African Economies - Lucas O. Elumah; Rahmon Abiodun Folami (Binus Business Review, 2026)
The research examined financial development and current account sustainability in African economies using panel data from 2010 to 2023 from the World Development Indicators (WDI). Unlike previous studies that focused narrowly on single indicators or on other regions, this research adopted a multidimensional approach by analyzing credit to the private sector, broad money supply, stock market capitalization, Foreign Direct Investment (FDI), and terms of trade and exchange rate dynamics. To address endogeneity and capture the persistence of current account positions, the researchers employed a dynamic panel Generalized Method of Moments (GMM) framework, ensuring robust and reliable results. The findings reveal strong persistence in current account balances, suggesting structural factors that maintain external positions over time. Among financial development variables, money supply has a statistically significant and positive effect, indicating that monetary deepening supports external sustainability. In contrast, credit to the private sector and stock market capitalization are statistically insignificant, reflecting shallow and inefficient financial systems across much of Africa. FDI exerts a positive influence, but its effectiveness depends on alignment with national development priorities. Terms of trade and exchange rate changes show weak and inconsistent impacts, underlining the region’s vulnerability to commodity dependence and external shocks. The research contributes novelty in three respects: incorporating multiple dimensions of financial development, providing region-specific evidence for African economies, and applying a dynamic panel GMM framework to strengthen methodological rigor. The results highlight the need to deepen financial institutions, promote export diversification, and enhance regional integration to improve external resilience and long-term macroeconomic stability.